Aplikasi Ko-Kemoterapi Fraksi Etil Asetat Ekstrak Etanolik Daun Sambung Nyawa (Gynura procumbens (Lour.) Merr.) Pada Sel Kanker Payudara MCF-7 - Jenie, Riris Istighfari; Meiyanto, Edy (Majalah Ilmu Kefarmasian, 2009)
Combination chemotherapy has been an interesting attention in recent years to cure cancer e.g. non-toxic or less toxic phytochemicals are being combined with chemo-therapeutic agents to sensitize cancer cell and to enhance the efficacy of chemothera-peutic agents as well as to reduce its toxicity to normal tissues. The aim of this research is to examine whether ethyl acetate fraction of Gynura procumbens ethanolic extract (SEF) synergizes the therapeutic potential of doxorubicin (Dox) on breast cancer cell line MCF-7. MTT assay were used to measure the growth inhibitory effect of the combination therapy on MCF-7 cells. SEF (5-250 µg/ml) treatment of cell resulted in 15-76% growth inhibition in a dose dependent manner (IC50 85 µg/ml), while Dox (10-100 nM) treatment did not show any inhibitory effect. The combina-tions of SEF (5-40µg/ml) with Dox (10-75 nM) seemed to not have any synergistic efficacy towards cell growth inhibition. Nevertheless, this result need further observa-tion regarding the IC50 of Dox on MCF-7 has not been determined yet. The cell characterization may influence the result. Doxorubicin could induce Akt survival apoptosis pathway in MCF-7 resulting resistancy of the cell towards doxorubicin.